The Response of Shallot (Allium ascalonicum) to Salinity Stress - Trisnaningsih, Umi; Sidik, Johan; Saleh, Ismail (Ann Publisher, 2023)
Shallot (Allium ascalonicum) cv Bima Brebes is the cultivar that was most widely cultivated in shallot production centers on Java Island. The increasing rate of land use conversion from agricultural to non-agricultural land caused the shallot cultivation to be directed to marginal lands, including land with high salinity. This study aimed to determine the effect of the salinity level on the growth and yield of shallots and to determine the highest level of salinity that can be tolerated by shallots. This experiment was carried out from October to December 2022 at the Experimental Station of Swadaya Gunung Jati University. The location is located in Cirebon City, West Java, Indonesia. The research method used was the experimental method with a completely randomized design (CRD). The treatment was salt concentration consisted of 5 levels i.e., 0 ppm, 1250 ppm, 2500 ppm, 3750 ppm, and 5000 ppm. Each treatment was repeated 5 times so that there were 25 experimental units. Each experimental unit consisted of 10 polybags of shallot plants. The results showed that salt concentration significantly inhibits the growth and yield of shallot at all of the measured parameters i.e., plant height, number of leaves, root length, root volume, plant dry weight, plant growth rate, number of tubers, tuber diameter, fresh tuber weight, and dry tuber weight. The salt concentration of 1250 ppm is the tolerance limit for salinity stress for shallots.